Analisis Tingkat Kepuasan Pedagang Terhadap Tata Kelola Pasar Lubuk Buaya oleh Dinas Perdagangan Kota Padang - Jerry Wahyu Nugraha; M Fachri Adnan (Jurnal Teori dan Riset Administrasi Publik, 2023)
This study aims to analyze the level of trader satisfaction with the governance of Lubuk Buaya Market. The background of this research is since Lubuk Buaya Market was only revitalized last year. However, it is known that in general the level of trader satisfaction is still relatively low, because the revitalization is still uneven and there are still shortcomings. Therefore, the satisfaction of traders must be considered by the manager so that traders feel comfortable in Lubuk Buaya Market. In this study, researchers used a quantitative approach with a descriptive method in Lubuk Buaya Market. The data obtained were collected through the process of questionnaire distribution, observation and documentation studies. The results showed that governance from the manager is very influential on trader satisfaction.